Measuring the continuing care needs of inpatients in rural China - Haoran Liu; Zhifan Wang; Juan Hu; Qiushuang Xu; Lei Yang; Weiyan Jian (BMC, 2024)
Abstract Background International experience shows that the suitability of a high-performance healthcare system for its given purposes is reflected in its ability to provide a continuum of services that match the changing health status of the given population. Although many low- and middle-income countries have sought to bring movement away from hospital-centered and towards patient-centered healthcare, such efforts have often had poor results, and one of the major reasons for this is the inability to accurately identify which inpatients need continuing care and what kind of continuing of care is needed. Objectives To measure and assess the continuing care needs of discharged patients and its influencing factors in rural China. Methods Data were obtained from the hospital database of Medical Center M in County Z from May to July 2022. County Z is a county of 1 million people in central China. The database includes basic patient information, disease-related information, and information on readiness for hospital discharge. Factors related to the need for continuing care were included in the analysis. The Readiness for Hospital Discharge Scale was used to assess the need for continuing care. The statistical data are expressed in terms of both frequency and composition ratio. Finally, linear regression was used to analyze the factors influencing the need for continuing care. Results The analysis included a total of 3,791 patients, 123 of whom (3.25%) had continuing nursing needs. The need of continuing nursing was related to patients' age group, mode of admission, occupation and major diagnostic categories (P < 0.05). Conclusions Developing continuing care is an important initiative for bridging the fragmentation of health services, and an appropriate supply system for continuing care, interconnected with inpatient services, should be established in rural areas in China as soon as possible. And provide more appropriate care for patients in need.